BNg3F3: the first three noble gas atoms inserted into mono-centric neutral compounds – a theoretical study. Issue 26 (15th June 2016) - Chen, Wei; Chen, Guang-Hui; Wu, Di; Wang, Qiang
Abstract : Following the study of HXeOXeH and HXeCCXeH, in which two Xe atoms were inserted into H2 O and C2 H2 theoretically and experimentally, the structures and stability of BNg3 F3 (Ng = Ar, Kr and Xe), in which three Ng atoms are inserted into BF3, have been explored theoretically using DFT and ab initio calculations. Abstract : Following the study of HXeOXeH and HXeCCXeH, in which two Xe atoms were inserted into H2 O and C2 H2 theoretically and experimentally, the structures and stability of BNg3 F3 (Ng = Ar, Kr and Xe), in which three Ng atoms are inserted into BF3, have been explored theoretically using DFT and ab initio calculations. It is shown that BNg3 F3 (Ng = Ar, Kr and Xe) with D 3h symmetry are local minima with short B–Ng bond lengths of 1.966, 2.027 and 2.214 Å at the CCSD(T)/aug-cc-pVTZ/LJ18 level, which are close to their covalent limits. Note that although BNg3 F3 (Ng = Kr and Xe) are energetically higher than the dissociation products 3Ng + BF3, they are still kinetically stable as metastable species with protecting barriers of 13.38 and 17.99 kcal mol −1 for BKr3 F3 and BXe3 F3 . Moreover, BKr3 F3, the tri-Kr-inserted compound, even has comparable kinetic stability to HXeOXeH and HXeOXeF. In addition, upon the formation of BNg3 F3, there is a large amount of charge transferred from B to Ng of at least 0.619 e . The calculated Wiberg Bond Indices (WBI) suggest that B–Ng bonds are naturally singly bonded; the large vibrational frequencies of B–Ng and Ng–F stretching modes and the negative Laplacian electron density of B–Ng bonds confirm further that BNg3 F3 are stiff molecules with covalent B–Ng bonds. It should be noted that three Ng atoms inserted into mono-centric neutral molecules have not been reported previously. We hope that the present theoretical study may provide important evidence for the experimental synthesis of BNg3 F3 .